Effectiveness of radiofrequency ablation for treatment of plantar fasciitis. Issue 12 (25th March 2022) - Kurtoglu, Alper; Kochai, Alauddin; Inanmaz, Mustafa Erkan; Sukur, Erhan; Keskin, Dogan; Türker, Mehmet; Sen, Zafer; Daldal, Ismail; Avan, Laçin Yüksel
Abstract : Abstract: Plantar fasciitis is the most common cause of heel pain. Pain can be persistent in some patients and interrupt daily activities and sportive activities. There are a lot of treatment options available for plantar fasciitis. We hypothesized that patients with chronic persistent plantar fasciitis can be successfully treated with radiofrequency nerve ablation (RFNA). Two hundred sixty-one patients with plantar fasciitis (378 feet) treated with RFNA from February 2017 to January 2019 were retrospectively assessed. All the patients had plantar heel pain for at least 6months. Based on their body mass index (BMI), the enrolled patients were divided into obese (BMI ≥ 30kg/m 2 ) and non-obese (BMI < 30kg/m 2 ) groups. The patients were asked to complete a questionnaire just before and after the procedure and during the final follow-up. The BNS Radiofrequency Lesion Generator was used during a single session. The patients' information, including their visual analogue scale (VAS) score and American Orthopaedic Foot and Ankle Society (AOFAS) score, was assessed. During their final follow-up, the patients were asked to rate the success of their treatment by choosing one of the following options: completely successful, very successful, moderately successful, marginally successful, or not successful. The VAS and AOFAS scores of all the patients were evaluated pre-procedure, in the first month after procedure, and during the final follow-up (8-24 months). There was a statistically significant difference between the pre-procedure and postprocedure VAS scores ( P < .001), there was no statistically significant difference between the VAS scores in the first month postprocedure and during the final follow-up. There was a statistically significant difference between the pre-procedure and postprocedure AOFAS scores ( P < .001), there was no statistically significant difference between the AOFAS scores in the first month postprocedure and during the final follow-up. RFNA can be used as an alternative method to surgical procedures for treating plantar fasciitis because it is safe and effective. The advantages of RFNA are that patients can quickly return to their work and resume weight-bearing activities.